Gongronema latifolium Lowers Blood Glucose via Pancreatic Islet Cell Regeneration and Insulin Sensitization - Al-Hindi, Bassel; Atangwho, Item Justin; Md Yusoff, Nor Adlin; Ahmad, Mariam; Asmawi, Mohd Zaini; Mun, Fei Yam (2014)
Objective: Gongronema latifolium is one of the African folk medicines for diabetes mellitus. Previous studies justified its use based on its antioxidant and glucose lowering potential. This study evaluated the effect of Gongronema latifolium ethanolic extract on blood glucose tolerance, β-cell effect, and in vitro glucose uptake. Materials and Methods: Whole dried G. latifolium was extracted using a soxhlet apparatus. Diabetes was induced by intraperitoneal injection of streptozotocin (55mg/kg). The diabetic rats were used for a 14-day study. Effects on abdominal muscle glucose uptake and intestinal glucose transport were investigated in vitro. Results: A 14-day oral administration of the extract (1mg/kg b.w.) to diabetic rats significantly attenuated the elevated blood glucose levels starting from day-10 till end of study (P<0.05). Unlike metformin, the 14-day oral treatment with- 1 g/kg and 0.5 g/kg of the extract caused 44% and 50% increases in the average area of the islets of Langerhans, respectively. The extract was also found to increase muscle glucose uptake significantly in the presence of insulin, indicating an insulin-sensitizing potential, which conformed to results related to serum insulin levels. Conclusion: Overall, data from this study, besides validation of the antidiabetic action of Gongronema latifolium suggest that the anti-diabetic activity is established via combined pancreatic and extra-pancreatic mechanisms mediated probably by the Sitostenone and fatty acid esters predominant in the extract.